A Culturally-Informed Family Role Model: A Conceptualising Family Influences in Children’s Cognitive, Emotional and Social Development (Sains Humanika, 2025)
Children’s cognitive, emotional, and social development is fundamentally shaped by the family environment, which provides the primary context for early learning, emotional security, and socialisation. While existing developmental theories offer valuable insights into family influence, many are grounded in Western assumptions and give limited attention to cultural variation in family roles and practices. In multicultural societies such as Malaysia, children’s development is closely intertwined with diverse family structures, parenting practices, and culturally embedded values. This concept paper introduces the Culturally-Informed Family Role Model (CIFRM), a framework that reorganises established developmental theories around the culturally mediated enactment of family roles. Drawing on Bronfenbrenner’s ecological systems theory, Vygotsky’s sociocultural theory, and Bandura’s social cognitive theory, CIFRM conceptualises parents, siblings, and extended family members as interdependent agents whose roles operate within specific cultural, structural, and contextual conditions to shape children’s developmental outcomes. The model was developed through thematic and comparative analysis of existing literature, positioning cultural values as a central mechanism rather than a peripheral context in child development. Presented using a tree metaphor to illustrate interconnected developmental influences, CIFRM offers a holistic lens for understanding family influence across cognitive, emotional, and social domains. The paper outlines implications for family practices, education, policy, and future empirical research, contributing a culturally grounded framework for supporting children’s development in diverse social contexts.
Keywords: Children development, family roles, cognitive development, emotional development, social development, cultural values, and CIFRM